Neurocognitive and linguistic development in bilingual children: a cross-sectional study on the impact of dual language exposure in 100 Egyptian children - Rasha Sami; Maha Ahmed (Middle East Current Psychiatry)
Abstract Background Bilingual children have better language development and cognitive function. Examining these impacts in an Egyptian setting sheds light on the potential implications of dual language exposure on cognitive results. Aim The study aimed to evaluate and compare the executive function of monolingual and bilingual children aged 5 to 7 to check the effect of bilingualism on cognitive abilities. Methods A cross-sectional analysis was conducted on 100 children from two schools in the 6th of October City, divided into monolingual (group 1) and bilingual (group 2) groups. Socioeconomic factors were analyzed, and language development was assessed using the Preschool Language Scales (PLS-5) for English and the Receptive-Expressive Arabic Language Scale (REAL Scale) for Arabic. The Stanford-Binet Intelligence Scales (SB-5) were also administered and then compared between the IQ subtests of both groups. Results Bilingual children scored significantly higher than monolinguals in Full-Scale IQ (113 ± 2 vs. 110 ± 4, p < 0.001), non-verbal IQ (117 ± 3 vs. 110 ± 2, p < 0.001), verbal IQ (112 ± 1 vs. 109 ± 2, p < 0.001), and working memory (112 ± 1 vs. 105 ± 3, p < 0.001). Both groups showed typical Arabic language development, and bilingual children also demonstrated age-appropriate English proficiency. Conclusion Bilingual children have different levels of language competency, and being bilingual affects how their language skills and cognitive abilities grow. The results of standardized tests indicate that bilinguals have a significant cognitive advantage, particularly in areas such as working memory and reasoning. Keywords: Stanford-Binet Intelligence Scales, Linguistic growth, Being monolingual, Being bilingual.